1995
DOI: 10.1177/030802269505800711
|View full text |Cite
|
Sign up to set email alerts
|

Snoezelen: Its Effects on Concentration and Responsiveness in People with Profound Multiple Handicaps

Abstract: This article is an initial investigation into the effects of Snoezelen on concentration and responsiveness in people who have profound and multiple handicaps. Eight subjects with profound learning disabilities took part. Ratings of concentration were recorded at each session using a simple task. The subjects were also assessed at every fifth session for responsiveness to the Snoezelen environment. The results suggest that all the subjects except one, who failed to score, responded In some way with improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 2 publications
1
47
0
1
Order By: Relevance
“…Only one other condition (relaxation therapy) produced similar positive effects on concentration levels. However, these effects only extended from the baseline to the probe assessment taken during mid-treatment, whereas the effects of Snoezelen| were significant at the probe assessment, as well as at the end of therapy, closely approximating the results of Ashby et al's (1995) research.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Only one other condition (relaxation therapy) produced similar positive effects on concentration levels. However, these effects only extended from the baseline to the probe assessment taken during mid-treatment, whereas the effects of Snoezelen| were significant at the probe assessment, as well as at the end of therapy, closely approximating the results of Ashby et al's (1995) research.…”
supporting
confidence: 53%
“…This in part stems from Snoezelen's| creators who initially argued that attempts to empirically evaluate Snoezelen| would contradict the very spirit in which it was created (Haggar & Hutchinson, 1991;Hulsegge & Verheul, 1987). In its infancy, the reputed positive effects of Snoezelen| were largely based on anecdotal evidence and informal investigations (Ashby et al, 1995). However, as Snoezelen| became more prevalent its credibility necessitated scientific study.…”
mentioning
confidence: 99%
“…Several uncontrolled studies have suggested that persons with mental retardation might benefit from Snoezelen in some of the ways described above (Ashby et al, 1995;DeBunsen, 1994;Hagger & Hutchinson, 1991). However, all of these studies lacked control conditions, and used non-blind measurement or retrospective data collection.…”
Section: Snoezelenmentioning
confidence: 99%
“…Studies have varied in the measures that they have used to assess the effects of multi-sensory therapy sessions, but the benefits which have been reported include: positive changes in behaviour Long & Haig, 1992); improved task concentration (Ashby et al, 1995;Lindsay et al, 1997); an increase in a variety of skills such as awareness of self, social interaction behaviours, communication, exploration and manipulation of stimuli (Houghton et al, 1998); relaxation (Slevin & McClelland, 1999); and a reduction in stereotypic self-stimulatory behaviours and an increase in adaptive behaviours such as exploratory behaviour or initiating contact with others (Shapiro et al, 1997).…”
Section: Learning Disabilitiesmentioning
confidence: 99%
“…Its aim is to be a relaxing activity, designed 'to create a feeling of safety, novelty and stimulation which is under the user's control' (Ashby et al, 1995) and in which there are no expectations for performance (Box 2).…”
mentioning
confidence: 99%